Pengaruh Persentase Fly Ash terhadap Sifat Fisik dan Mekanik Papan Beton Ringan dengan Filler Serat Sabut Pinang - Hana Aulia; Alimin Mahyudin (Jurnal Fisika Unand, 2024)
Research has been conducted on the effect of fly ash percentage towards physical and mechanical characteristics of lightweight concrete board with coir fiber as a filler. The study was aim to determine the effect of fly ash percentage with areca fiber as a filler on the physical and mechanical properties of lightweight concrete boards. The percentages of fly ash were 0%; 5%; 10%; 15%; and 20% respectively. The size of areca fiber was 0.2%, and the length of the fiber was 1 cm. Samples with 5 cm x 5 cm x 1 cm were used to measure density, porosity, and compressive strength, while samples with 20 cm x 5 cm x 1 cm were used for flexural strength testing. The lightweight concrete board was tested after 28 days. Compressive and flexural strength testing were conducted using a universal testing machine (UTM). Based on the results, the lowest density value was obtained at 20% fly ash content which was 1.06 g/cm3, while the lowest porosity value was obtained at 0% fly ash content which was 26.53%. The density values obtained from the research results were inversely related to the porosity values. The highest compressive strength of lightweight concrete boards without fly ash was achieved, with a value of 36.93 kg/cm2. The highest compressive strength value with fly ash was 30.20 kg/cm2 at 10% fly ash content. The highest flexural strength was 25.5 kg/cm2 at 20% fly ash content. The higher the fly ash content used, the greater the flexural strength value. The density and flexural strength values have met the SNI 03-2105-2006 and SNI 03-2104-1991 standards, but the porosity and compressive strength have not yet fulfilled the SNI standards.